Measures adopted by Principals in Public and Private Secondary Schools in Enugu State for Effective Evaluation of Students’ Learning Experience. (UNIZIK Journal of Educational Management and Policy, 2025)
The seeming decline in the quality of education in Nigeria necessitated this study on evaluation of students’ learning experience measures in public and private secondary schools in Enugu State: implications for quality assurance. The study adopted the descriptive survey research design. One research question guided the study while one hypothesis was tested at 0.05 level of significance. The population of the study comprised 25,579 respondents made up of 8,362 teachers in public secondary schools in Enugu State and 17, 217 private secondary school teachers in Enugu State. The sample for the study comprised of 773 (382 public and 391 private) teachers. A researcher developed questionnaire was the instrument used for data collection. The instrument was validated by three experts, one in Educational measurement and evaluation, Department of Educational Foundation and the others in Educational planning and management, Educational Management and Policy Department all in the Faculty of Education Nnamdi Azikiwe University, Awka. The Cronbach’s alpha method was used to determine the internal consistency of the items and it yielded a reliability coefficient of 0.76. The researchers with the help of eight research assistants distributed and successfully collected 773 copies of the questionnaire administered. The research question was answered using the mean, while the hypothesis was tested using z-test at 0.05 level of significance. It was found out among others that principals in public and private secondary school principals in Enugu State adopt adequate measures in the evaluation of students’ learning experience. Based on the findings of the study, it was recommended among others secondary school principals should introduce a special wear for the students during examination to make sure they don’t bring in materials related to the examination.
Keywords: Evaluation of Learning Experience, Quality Assurance